Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/noajnl/vdaa140
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, single-arm, phase II trial of buparlisib in patients with melanoma brain metastases not eligible for surgery or radiosurgery—the BUMPER study

Abstract: Background Patients with melanoma brain metastasis (MBM) still carry a dismal prognosis. Preclinical data originated in xenograft models showed that buparlisib therapy was highly effective in therapy-naïve MBM. Patients and Methods In this open-label, phase II trial we investigate the safety and efficacy of monotherapy with buparlisib, a PI3K inhibitor, in patients with asymptomatic MBM that were not candidates for local ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The strong effects of the low preventive dose were confirmed using the second H1 melanoma model ( Supplementary Figure 5 ). In contrast to the findings with the preventive schedules, treating established metastasis with 12.5 mg/kg/d GNE-317 led only to moderate effects on the growth of established BMs ( Figure 5C-E ), which is in line with the lack of response of established BM when MM patients were treated with the PI3K inhibitor buparlisib 14 . These data imply that there is a substantial benefit of starting low-dose drug administration with GNE-317 during the earliest steps of brain colonization.…”
Section: Resultsmentioning
confidence: 47%
See 2 more Smart Citations
“…The strong effects of the low preventive dose were confirmed using the second H1 melanoma model ( Supplementary Figure 5 ). In contrast to the findings with the preventive schedules, treating established metastasis with 12.5 mg/kg/d GNE-317 led only to moderate effects on the growth of established BMs ( Figure 5C-E ), which is in line with the lack of response of established BM when MM patients were treated with the PI3K inhibitor buparlisib 14 . These data imply that there is a substantial benefit of starting low-dose drug administration with GNE-317 during the earliest steps of brain colonization.…”
Section: Resultsmentioning
confidence: 47%
“…These established human BM showed PAM pathway activation in many cases, but activation patterns were quite heterogenous ( Figure 3B ). Together with the biosensor study and in light of a clinical trial showing insufficient response to a PI3K inhibitor in MM patients with established BM 14 , this provided a clear rationale to experimentally test the BM-suppressive effects of GNE-317 in various schedules. Here, we hypothesize that the PAM pathway inhibitor has the strongest effects on early, fate-deciding steps of BM formation where the PAM pathway could play the most relevant and consistent role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate trial (BUMPER) evaluating the CNSpenetrable pan-PI3K inhibitor buparlisib in untreated MBM demonstrated that buparlisib monotherapy produced no intracranial responses in MBM patients unselected for PI3K pathway activation, although the drug itself was well tolerated (112). The MEK inhibitor binimetinib showed modest efficacy in a pilot study of 11 patients with NRAS mutated MBM who had failed multiple previous lines of therapy (113).…”
Section: All Authorsmentioning
confidence: 99%
“…Regarding specific therapeutics, we used drugs to inhibit the MAPK and BCL-2 family members. AKT was inhibited with siRNA, although there are a number of drugs blocking PI3K/AKT that are being tested in clinical trials for melanoma [57][58][59].…”
mentioning
confidence: 99%